2005
DOI: 10.1128/aac.49.8.3546-3549.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nystatin Induces Secretion of Interleukin (IL)-1β, IL-8, and Tumor Necrosis Factor Alpha by a Toll-Like Receptor-Dependent Mechanism

Abstract: Nystatin is an antifungal compound with potent proinflammatory properties. Herein, we demonstrate that nystatin induces interleukin (IL)-1␤, IL-8, and tumor necrosis factor alpha secretion through its activation of toll-like receptor 1 (TLR1) and TLR2. Hence, a TLR-dependent mechanism could serve as the molecular basis for the proinflammatory properties of nystatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…8). This level of inhibition is comparable to that found in at least two other studies where this mAb was used (32,33). The fact that the epitope for GD2.F4 maps to the outer loop of LRR11 confirms the importance of this region in receptor function.…”
Section: Discussionsupporting
confidence: 73%
“…8). This level of inhibition is comparable to that found in at least two other studies where this mAb was used (32,33). The fact that the epitope for GD2.F4 maps to the outer loop of LRR11 confirms the importance of this region in receptor function.…”
Section: Discussionsupporting
confidence: 73%
“…Nystatin was previously reported to induce pro-inflammatory cytokines via TLR1/TLR2 signaling [3] but we found that nystatin, as well as amphotericin B and natamycin, required LPS prestimulation to induce pro-IL-1β as a prerequisite for IL-1β secretion. Hence, or data argue against a direct agonistic role of these drugs on TLRs.…”
Section: Discussionmentioning
confidence: 60%
“…The nystatin model of paw edema induces chronic inflammation, which can last up to 15 days [199]. Nystatin triggers TLR-2 and induces secretion of TNF-α, IL-8, and IL-1β [200]. Based on more recent data from our laboratory [20], we would suggest that the reduced inflammation in this model was the result of creatine reducing expression of TLR-2 in vivo .…”
Section: Creatine As An Anti-inflammatory Agentmentioning
confidence: 99%